Digitization, innovation, and participation: digital conviviality of the Google Cultural Institute - Stone, Leah, author; Champ, Joseph, advisor; Seel, Pete, committee member; Amidon, Timothy, committee member; Guzik, Keith, committee member; Switzer, Jamie, committee member (Colorado State University. Libraries, 2018)
To view the abstract, please see the full text of the document.